PERBEDAAN HASIL BELAJAR FISIKA SISWA YANG MENGGUNAKAN LKS BERORIENTASI PADA KEMAMPUAN BERPIKIR INDUKTIF DENGAN KEMAMPUAN BERPIKIR DEDUKTIF - Aryati Liskaningsih; Syifaul Gummah; Intan Kusuma Wardani (Lensa: Jurnal Kependidikan Fisika, 2016)
This study aims to determine differences in physics student learning achievement which using the worksheet oriented thinking abilityinductive with deductive. This research is experimental research (quasy experimental design). The study population was all students of class X in SMKN 3 Mataram with the study sample consisted of two classes, X GEO B and X TSM B. X GEO B class taught using worksheet  oriented thinking ability inductive and X TSM B class taught using worksheet oriented thinking ability deductive. Instruments in this study using multiple-choice test. The results of post-test data analysis obtained the average value of the two classes of samples is 81.27 (X GEO B) and 72.25 (X TSM B) so obtained tcount = 3.56, while ttable = 2.00 at significance level of 5% so that the alternative hypothesis (Ha) accepted. These results show that there are differences in physics learning outcomes of students who use the worksheet oriented thinking ability inductive with deductive.